2017
DOI: 10.1109/ted.2017.2703809
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gate–Drain Spacing on Low-Frequency Noise Performance of <italic>In Situ</italic> SiN Passivated InAlGaN/GaN MIS-HEMTs

Abstract: In this paper we investigated the gate-drain access region spacing (L GD) effect on electrical and noise performance of InAlGaN/GaN metalinsulator-semiconductor high electron mobility transistors (MIS-HEMTs) using in situ SiN cap layer as gate insulator. Different L GD of InAlGaN/GaN MIS-HEMTs using sub-10 nm barrier layer are studied. Low-frequency noise measurements have been carried out for the first time in order to analyze the impact of the gate-drain spacing on the electrical characteristics. The noise o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Similar dependence over V GS -V TH indicating the dominant channel noise is located under the gate, as reported in previous works [25,26]. In [27], the channel noise under the gate was also the main contribution of the total channel noise for for low gate-drain access region spacing L GD < 10 µm.…”
Section: Methodssupporting
confidence: 85%
See 2 more Smart Citations
“…Similar dependence over V GS -V TH indicating the dominant channel noise is located under the gate, as reported in previous works [25,26]. In [27], the channel noise under the gate was also the main contribution of the total channel noise for for low gate-drain access region spacing L GD < 10 µm.…”
Section: Methodssupporting
confidence: 85%
“…In agreement with these results, it can be pointed out that the current collapse level within these devices as assessed by pulsed measurements has been found to be similar regardless of the SiN cap layer thickness. We previously analyzed S ID /I D 2 dependence over the gatedrain spacing of InAlGaN/GaN MIS-HEMTs by considering two noise sources in the channel: channel noise under the gate and channel noise in the gate-drain access regions [27].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-frequency noise (LFN) measurement for AlGaN/GaN HEMTs is an efficient tool to exam device performance, analyze material defects, and study device reliability [5][6][7][8]. Many research groups have reported by investigating the effects of in situ/ex situ passivation layers [9,10], the gate-to-drain distance [7], and the types of GaN buffer layer [11] on the LFN of AlGaN/GaN HEMTs.…”
Section: Introductionmentioning
confidence: 99%
“…Low-frequency noise (LFN) measurement for AlGaN/GaN HEMTs is an efficient tool to exam device performance, analyze material defects, and study device reliability [5][6][7][8]. Many research groups have reported by investigating the effects of in situ/ex situ passivation layers [9,10], the gate-to-drain distance [7], and the types of GaN buffer layer [11] on the LFN of AlGaN/GaN HEMTs. M. D. Hasan, et al [6] demonstrated that the AlGaN/GaN metal-oxide-semiconductor (MOS)-HEMT with Al composition of 20% exhibited a lower noise level than that of the device with Al composition of 35%.…”
Section: Introductionmentioning
confidence: 99%